2009
DOI: 10.1111/j.1478-3231.2009.02086.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological actions of curcumin in liver diseases or damage

Abstract: Since 1900 BC, several therapeutic activities have been attributed to the rhizomes of the plant Curcuma longa for a variety of diseases, including liver disorders. Curcumin, the main active compound obtained from this plant, was first isolated two centuries ago and its structure as diferuloylmethane was determined in 1910. Curcumin has shown anti-inflammatory, anti-oxidant, antifungal, antibacterial and anticancer activities. The pharmacological properties of curcumin were reviewed recently and focused mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(89 citation statements)
references
References 93 publications
5
82
0
2
Order By: Relevance
“…Because of its lack of toxicity, there has been increasing interest in further studies with curcumin [12,13]. Unfortunately, its poor absorption undermine its clinical potential [14].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its lack of toxicity, there has been increasing interest in further studies with curcumin [12,13]. Unfortunately, its poor absorption undermine its clinical potential [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, a review of literature revealed that none of the herbal medications that patient 1 had taken (Lineum usitatissimum, Fumariaceae, Curcumin, and Silybum marianum) are known to cause a liver damage; in fact, several recent studies have shown a protective effect of these medications in states of liver injury. [21][22][23][24] Nevertheless, no study examined the combination of these herbal medications, thus, potential liver toxicity cannot be excluded. As to the second patient who was treated with fluconazole, although LFT abnormalities are associated with all of the azoles, these abnormalities are more likely with itraconazole and ketoconazole than with fluconazole 25,26 and the later seems to have a lower risk of treatment discontinuation because of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…The polyphenol curcumin has been shown to be an effective treatment for liver and lung fibrosis both in vivo and in vitro (Bruck et al, 2007;Venkatesan et al, 2007;Rivera-Espinoza and Muriel, 2009). It prevents fibrosis by blocking leukocyte influx, inhibiting the activation of inflammatory cells and subsequent release of proinflammatories.…”
Section: Discussionmentioning
confidence: 99%